2010
DOI: 10.1007/s10545-010-9097-3
|View full text |Cite
|
Sign up to set email alerts
|

Differential HMG‐CoA lyase expression in human tissues provides clues about 3‐hydroxy‐3‐methylglutaric aciduria

Abstract: 3-Hydroxy-3-methylglutaric aciduria is a rare human autosomal recessive disorder caused by deficiency of 3-hydroxy-3-methylglutaryl CoA lyase (HL). This mitochondrial enzyme catalyzes the common final step of leucine degradation and ketogenesis. Acute symptoms include vomiting, seizures and lethargy, accompanied by metabolic acidosis and hypoketotic hypoglycaemia. Such organs as the liver, brain, pancreas, and heart can also be involved. However, the pathophysiology of this disease is only partially understood… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(26 citation statements)
references
References 39 publications
0
25
1
Order By: Relevance
“…All procedures followed were in accordance with the ethical standards of the responsible committee on human experimentation of The First Hospital of Jilin University (Changchun, China) and with the Helsinki Declaration of 1975, as revised in 2000 (7). Informed consent was obtained from the parents of the patient.…”
Section: Case Reportmentioning
confidence: 99%
See 1 more Smart Citation
“…All procedures followed were in accordance with the ethical standards of the responsible committee on human experimentation of The First Hospital of Jilin University (Changchun, China) and with the Helsinki Declaration of 1975, as revised in 2000 (7). Informed consent was obtained from the parents of the patient.…”
Section: Case Reportmentioning
confidence: 99%
“…In the absence of HL, leucine cleavage is incomplete, resulting in accumulation of metabolic acids and compromised ketone body synthesis (6). Elevated levels of metabolic acids often cause liver damage and/or hepatomegaly in 3-HMG patients (7). Normally, during periods of fasting or infection, generation of ketone bodies in mitochondria provide an alternative energy source for the brain, heart and kidney (6).…”
Section: Introductionmentioning
confidence: 99%
“…However, its distribution and activity in human tissues have been limited to enzyme assay in fibroblast (Wanders et al, 1988b) lymphoblast (Wysocki et al, 1976b) liver biopsy (Robinson et al,1980) amniocytes and chorionic villi (Wanders et al, 1988b) or pancreatic islets (MacDonald et al, 2007). Recently, it has been reported the first study of mRNA levels, protein expression and enzyme activity of human HMG-CoA lyase in kidney, pancreas, testis, heart, skeletal muscle and brain (Puisac et al, 2010). The highest HL activity was found in liver and pancreas was the second with more activity (Figure 4c).…”
Section: Enzyme Expressionmentioning
confidence: 99%
“…It has been reported that organs such as the brain, the liver and occasionally the pancreas and the heart are affected (Gibson et al, 1994;Leung et al, 2009;Muroi et al, 2000a;Urganci et al, 2001;Wilson et al, 1984;Zafeiriou et al, 2007;Zoghbi et al, 1986). Recently, a study of mRNA levels, protein expression and enzyme activity of human HMG-CoA lyase in kidney, pancreas, testis, heart, skeletal muscle and brain has contributed to better understanding of the enzyme function and of the involvement of these organs in 3-hydroxy-3-methylglutaric aciduria (Puisac et al, 2010). The liver is the organ most frequently affected in this deficiency, although involvement is usually mild, with elevated transaminases and hepatomegaly (Urganci et al, 2001;Wysocki & Hahnel, 1986).…”
Section: Chronic Complicationsmentioning
confidence: 99%
See 1 more Smart Citation